Effect of Si3N4 nanoparticulates on the mechanical and electrical properties of PZT ceramics - Orapim Namsar (2018)
PZT/xSi3N4 ceramics (when x=0, 0.1, 0.5 and 1 wt.%) were prepared by a solid-state mixed-oxide method and sintered at 1125 °C for 2 h. X-ray diffraction results suggested that the addition of Si 3N4 nanoparticulates did not significantly affect the unit cell and tetragonality of PZT. The addition of 0.1 wt.% Si3N 4 effectively increased the density and reduced the grain size of PZT ceramics. These changes played an important role in hardness and fracture toughness improvement. The maximum room temperature dielectric constant was achieved in a PZT/0.1 wt.% Si3N4 sample. Within the Si3N4-containing samples, the high-temperature dielectric values and ferroelectric properties seemed to increase with increasing concentrations of Si3N4. © 2010 The Royal Swedish Academy of Sciences.